IPM in wheat for increased productivity and profitability - Sharma, A K; Babu, K Srinivasa; Saharan, M S; Singh, Randhir; Singh, S S (Indian Farming, 2015)
The IPM technology has been developed and validated at the farmers’ fields in wheat. This technology is initiated only in the recent past in case of wheat. IPM has been introduced in wheat by the DWR, Karnal under four phases, covering synthesis, evaluation/validation, large scale promotion at farmers’ fields. During the fourth phase, the Extension Unit of Directorate has taken up this technology for transfer to the farmers’ fields in various districts of Haryana. Since, there are several pest problems common to rice and wheat crops and the tillage options of one crop affect the pest system in the other, it has been recommended that the IPM approach may be adopted on cropping system basis rather than individual crop basis. The yield advantages in the last decade have indicated a yield gain of about 10%.